Is mushroom polysaccharide extract a better fat replacer than dried mushroom powder for food applications? - See Toh, Cheryl Jie Yi; Bi, Xinyan; Lee, Hui Wen; Yeo, Michelle Ting Yun; Henry, Christiani Jeyakumar (Frontiers in Nutrition, 2023)
β-glucans found in the cell walls of mushrooms can be a beneficial food additive in replacing fat in commercial food products. Four commonly consumed mushroom species in Singapore, i.e. Pleurotus ostreatus spp., Lentinus edodes, Agaricus bisporus, and Flammulina velutipes were profiled for the β-glucan content in the lyophilized form and ultrasonicated assisted extracted form. Both forms were added into chicken patties, which were characterized for the moisture, cooking loss, texture, colour, and chemically analysed for the protein, crude fat, and fatty acid profiles with gas chromatography mass spectrometry (GC-MS). Pleurotus Ostreatus spp. had the highest β-glucan of 29.8 ± 0.7 g/100 g in the pure powder form and 15.9 ± 0.3 g/100 g from the extract. Crude fat in 100% fat substituted patties was lowest in Flammulina velutipes extract enriched patties (1.6 ± 0.3%) and least in A. bisporus pure powder patties at 1.5 ± 0.3%. Additionally, fat replacement with A. bisporus extract and powder forms resulted in the highest polyunsaturated fatty acid profile of 49.6 ± 1.9 mg/100 g patty and 79.9 ± 4.5 mg/100 g patty, respectively. Chicken patties with added mushroom extract were notable in retaining moisture, cooking yield and its structure. Fat substitution with mushroom powder was also conducted, satisfactory results indicated a possibility as a better fat replacer that is easily processed and an efficient alternative to β-glucan extract. With increasing demand for low fat foods with acceptable organoleptic properties, our study demonstrates that the inclusion of dry mushroom powder has the ability to mimic the ‘fattiness’ of chicken patties.